Managed by the algorithm: platform discourse, entrepreneurial subjectivity, and precarity among Indonesian gig workers - Abdul Wahid (CV Narasi Khatulistiwa Indonesia, 2026)
Background: Algorithmic management has expanded across Indonesia’s gig economy, where platform narratives of flexibility, partnership, and opportunity coexist with informal employment, unstable protection, and digitally mediated control. Objective: This study examines how official platform discourse constructs entrepreneurial subjectivity and organises precarity among Indonesian gig workers. Method: A qualitative critical discourse design was applied to twenty-one public documents comprising platform terms, recruitment pages, driver communications, corporate releases, verified reporting, scholarly materials, and policy documents, analysed through discourse framing, subject-positioning, and precarity-and-control matrices. Results: Findings show that welfare, flexibility, and recognition legitimise platform participation by presenting conditional benefits and operational choice as evidence of partnership. Workers are simultaneously positioned as autonomous, calculative, self-investing, resilient, and responsible for converting platform opportunities into sustainable livelihoods. Implication: However, tariff setting, performance metrics, benefit eligibility, account governance, risk transfer, information asymmetry, and protection gaps delimit this autonomy and distribute uncertainty disproportionately towards workers. Novelty: This study contributes a relational account of platform labour by conceptualising conditional entrepreneurial autonomy as a discursive and institutional arrangement through which limited operational discretion coexists with concentrated infrastructural authority, thereby integrating language, subject formation, and algorithmic governance within one analytical framework in a Global South setting often examined mainly through employment relations, technical systems, or workers’ experiences.